2016 Computing in Cardiology Conference (CinC) 2016
DOI: 10.22489/cinc.2016.243-411
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anti:arrhythmic Effects of Combined Blockade of Sodium and Ultra:rapid Delayed Rectifier Potassium Channels in Human Atria

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Along this line, Ni et al (2017b) studied in silico the effects of the multi-channel blockers on atrial and ventricular activation, and found that the synergistic use of a specific and potentially selective IKur potassium channel blocker (acacetin) and a INA blocker seems to have no significant impact on QT prolongation or on ventricular activation. As suggested, the synergetic antiarrhythmic treatment leads to more effective termination of atrial reentries (Aguilar et al, 2015; Ni et al, 2016), while ventricular side effects in the ventricles are limited. Furthermore, the relationship between drug concentration and AF termination is also considered in other studies (Duarte et al, 2013; Tobón et al, 2014a, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Along this line, Ni et al (2017b) studied in silico the effects of the multi-channel blockers on atrial and ventricular activation, and found that the synergistic use of a specific and potentially selective IKur potassium channel blocker (acacetin) and a INA blocker seems to have no significant impact on QT prolongation or on ventricular activation. As suggested, the synergetic antiarrhythmic treatment leads to more effective termination of atrial reentries (Aguilar et al, 2015; Ni et al, 2016), while ventricular side effects in the ventricles are limited. Furthermore, the relationship between drug concentration and AF termination is also considered in other studies (Duarte et al, 2013; Tobón et al, 2014a, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, considering patients during SR, the effect of antiarrhythmic drugs, such as potassium or sodium channel blockers, on the APD or ionic current characteristics, has been studied (Wettwer et al, 2004; Ehrlich et al, 2008; Law et al, 2010; Aslanidi et al, 2012a; Marshall et al, 2012; Voigt et al, 2013; Ni et al, 2016; Skibsbye et al, 2016; Ellinwood et al, 2017b; Tobón et al, 2017). Ablation success, applied during SR, has been presented (Tobón et al, 2015; Bayer et al, 2016) and the changes occurring in the P-waves after the PV isolation procedure have also been examined (Saha et al, 2016).…”
Section: Resultsmentioning
confidence: 99%